FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN WANITA MENOPAUSE DI DESA KOTAYASA: THE FACTORS RELATED TO MENOPAUSE WOMEN’S ANXIETY IN KOTAYASA VILLAGE - Fitriani, Revica Nur; Utami, Tin; Dewi, Feti Kumala (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2023)
Introduction: In 2020, the Indonesian population will reach 262.6 million people, with the number of womenliving at the age of menopause amounting to 30.3 million people with an average age of 49 years. Women whoexperience the menopause period, there are indications of physical and psychological changes so that womenconsider themselves unattractive, unable to provide sexual satisfaction to their husbands, thus causing anxietyto menopausal women. The purpose of this study was to determine the factors that can affect the anxiety ofmenopausal women in Kotayasa Village.Method: Correlative analytical research design using a cross sectional approach. The research variables wereeducation, age, occupation, socioeconomics and anxiety. The research was conducted from October 2022 to August 2023 in Kotayasa Village. The study sample was 84 menopausal women aged 45-55 years obtainedthrough cluster sampling. The research instruments used knowledge questionnaires and HARS. Data analysisusing spearman rank test.Results: The results showed no significant relationship between education and anxiety (p = 0.466), age andanxiety (p = 0.996), occupation and anxiety (p = 0.689), and socioeconomics and anxiety (p=0.353). However,there was a significant relationship between knowledge and anxiety with a value of p=0.011 (p<0.05).Conclusion: Anxiety of menopausal women is only influenced by knowledge. Future researchers are expectedto analyze other factors associated with anxiety in menopausal women, using other research approaches ormethods to identify factors associated with anxiety in menopausal women.